Kreativitas Anak Usia 5-6 Tahun di TK Joy Kids National Plus Tasikmalaya - Nurhayati, Rika; Qonita, Qonita; Hendri Mulyana, Edi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to describe the level of creativity among children aged 5–6 years at TK Joy Kids National Plus Tasikmalaya, based on four main aspects: fluency, flexibility, originality, and elaboration. A quantitative descriptive method was used, involving 20 children as participants. The results showed that most children were at a moderate level of creativity, with notable strengths in generating many ideas (fluency) and coming up with unique ideas (originality). However, the ability to think from different perspectives (flexibility) varied among children, and the skill of developing ideas in more detail (elaboration) was still in progress. Based on these findings, it is recommended that learning strategies be adjusted to each child's needs and that the learning environment be made more stimulating to help develop their creativity more effectively. The implication of this study is the need to develop more flexible, contextual, and child-centered learning strategies to support the equal development and enhancement of all aspects of creativity—particularly flexibility and elaboration—while also acknowledging the limitation in generalizability, as the research was conducted at a single institution